Rare case of hepatocellular carcinoma metastasising to the pituitary and cavernous sinus causing panhypopituitarism and bilateral ophthalmoplegia. Issue 10 (27th October 2020) - Ambalavanan, Jayachidambaram; Peravali, Monica; Perry, David J
Abstract : Pituitary metastases, especially from a primary hepatocellular carcinoma (HCC), are rare. Review of the literature revealed only few cases reporting pituitary metastases complicated by panhypopituitarism from HCC. Calvarial metastases from HCC are even more rare. Here, we present a unique case of primary HCC with metastases to both the calvarium and the pituitary causing panhypopituitarism and bilateral ophthalmoplegia, respectively. To our knowledge, this is the first reported case of two unique and rare complications from metastatic HCC.